La triada oscura de la personalidad y su impacto en el liderazgo organizacional - Luna Victoria De Bona, Giancarlo (2024)
One of the main challenges for organizational psychology is to analyze the psychological variables that influence on the success of enterprises. Among this variables, personality and leadership are highlighted, and constitute the objects of study in the current review. Personality is addressed through the theory of the Dark Triad, while leadership is examined within the framework of the Trait Theory. The purpose of this is to analyze the impact of the dark triad of personality on organizational leadership. Following the PRISMA guidelines, the review was conducted using databases such as Scopus, Web of Science, Apa PsycNet, Proquest, and Ebsco. From this, ten quantitative articles were selected for detailed analysis. The findings reveal that the dark trait personality traits have both positive and negative impacts on leadership. Specifically, psychopathy and Machiavellian traits demonstrate negative effects, while the narcissistic trait may have positive implications for leadership. It is concluded that is essential to evaluate these traits within the organizational context when conducting performance evaluations, personnel selection, and other processes, taking into account their differentiating characteristics and their impact on both the organization and its employees.